التصريح بالممتلكات كآلية لمكافحة الفساد الاداري في التشريع الجزائري - زيدي, عبد االقادر; زيدي, عبد الله (University of Eloued جامعة الوادي, 2022)
يعتبر التصريح بالممتلكات عملة واحدة لها وجهان، فهو من جهة يعتبر كصون لنزاهة الأشخاص المكلفين بخدمة عمومية ومن جهة أخرى يؤدي إلى التشكيك في نزاهة كل مسؤول ممتنع عن تقديم التصريح بممتلكاته، حيث يعاقب كل موظف عمومي أخل بواجب التصريح بالممتلكات سواء بامتناعه عن تقديمه أو إذ قدمه لكنه خاطئ أو ناقص ويعاقب كذلك في حالة الزيادة الهائلة في ذمته المالية مقارنة بمداخيله المشروعة بحيث يعجز عن تبرير هذه الزيادة ، حيث يحال المخالفون على النيابة العامة لتحريك الدعوى العمومية عند الاقتضاء. وجعل المشرع الجزائري مهمة تلقي التصريحات بالممتلكات لذوي المناصب القيادية في الدولة بيد رئيس المحكمة العليا، بينما يقوم الموظفون العموميون بتقديم التصريح بممتلكاتهم أمام الهيئة الوطنية للوقاية من الفساد ومكافحته والتي تعتبر سلطة إدارية مستقلة، بحيث يكتتب الموظف العمومي تصريحا بممتلكاته العقارية و المنقولة ويقدمه أمامها مباشرة أو عن طريق السلطة السلمية أو الوصائية ويكون ذلك عند بداية و نهاية خدمته أو العهدة الانتخابية أو عند كل زيادة معتبرة في ذمته المالية خلال الآجال وبالكيفيات المحددة قانونا.Declaring property is considered one coin with two sides. On the one hand, it is considered as safeguarding the integrity of persons charged with a public service, and on the other hand, it leads to questioning the integrity of every official who refrains from submitting a declaration of his property, as every public official who violates the duty to declare property is punished, whether by his refusal to submit it or by submitting it. But he is wrong or incomplete, and he is also punished in the event of a huge increase in his financial liability compared to his legal income, so that he is unable to justify this increase, as the violators are referred to the Public Prosecution to initiate a public lawsuit when necessary. The Algerian legislator made the task of receiving property declarations for those in leadership positions in the state in the hands of the President of the Supreme Court, while public officials submit the declaration of their property before the National Authority for the Prevention and Control of Corruption, which is an independent administrative authority, so that the public official writes a declaration of his real and movable property and submits it directly to it or Through the peaceful authority or the guardianship, and this is at the beginning and end of his service or the electoral mandate, or upon every significant increase in his financial liability during the deadlines and in the ways specified by law.
مدكرة ماستر
Keywords: التصريح بالممتلكات ، آلية الوقاية ، الفساد الإداري ، التشريع الجزائري .; property declaration, prevention mechanism, administrative corruption, Algerian legislation